Does muscle energy technique have an immediate benefit for women with pregnancy‐related pelvic girdle pain?. (12th September 2018) - Ceprnja, Dragana; Gupta, Amitabh
Abstract: Objective: Pregnancy‐related pelvic girdle pain (PPGP) is a common and debilitating condition. Muscle energy techniques (METs) are used in the management of PPGP. This study aimed to determine the immediate effectiveness of a MET in the management of pain in women with PPGP within a single session of physiotherapy. Methods: This study was a randomized, crossover, sham‐controlled trial. Women ( N  = 80), M ( SD ), 30 (5) years of age and 29 (5) weeks of gestation with PPGP were included in the study. All participants were treated with a MET and sham transcutaneous electrical nerve stimulation in a randomized order, followed by standard physiotherapy during a single physiotherapy session. The primary outcome measures were the self‐report of pain using a visual analogue scale and function using the Timed Up and Go. The secondary outcome was the duration of single leg stance (SLS). Clinical measures were taken prior to the first intervention and immediately following each of the interventions, a total of four times. Results: There was no statistically significant difference between scores for the visual analogue scale, Timed Up and Go, or duration of SLS between participants following the use of a MET, sham transcutaneous electrical nerve stimulation, or standard care, which was recorded after each intervention ( p  ≥ 0.72). There was a consistent and statistically significant ( p value, mean difference) improvement in pain ( p  < 0.001, 2.6), function ( p  < 0.001, 1.0 s), and left SLS ( p  < 0.001, 4.4 s) and right SLS (p < 0.001, 4.7 s) from baseline compared with each time of measurement thereafter. Conclusions: The improvements measured may have been due to a placebo effect with the knowledge that care is being provided, mechanical unloading during the session, or familiarization with the test procedures. The mechanism(s) that led to improvements in pain and function remain unknown, however, does not preclude from women with PPGP being offered physiotherapy care.